INJURIES AMONG MALE AND FEMALE SCHOOL LEVEL CRICKET PLAYERS AND THEIR IMPACT ON PERFORMANCE - Kaushik, Akshay (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Objective: To compare the incidence and pattern of injuries among male and female school level cricket players, along with their impact on the players’ performance. Design: A comparative study. Study population: 400 male and female (200 each) cricket players between 15 to 19 years. Results: The statistical analysis revealed significant differences across various characteristics of players, highlighting gender disparities in sports engagement within the selected population. A significant majority of players sustained injuries while playing matches among male (86.0%) and female (85.0%) cricket players. It was observed that Abrasion (29.7%) was the most common type of injury among males, whereas female players highly reported Bruise (27.6%). Comparison of affected regions (according to OSICS classification) during injuries among male and female cricket players showed non-significant differences. Lower back (15.1%) among males and ankle (15.3%) among females were the significantly affected body parts. Analysing mechanism of injury, ’struck by ball’ was most reported among all. Fielding was seen most vulnerable playing position for the sustained injuries among male (59.9%) and female (52.9%) cricket players. Also, it was seen that more than half of the injured players in male (58.1%) and female (50.6%) cricket players were unable to continue playing or missed the match due to sustained injury. Conclusion: The findings highlight the significant impact of injuries in cricket, with variations observed between male and female players. Understanding injury patterns, risk factors, and prevention strategies is essential for improving player safety and performance in both genders. This research will help in understanding the need for developing gender-specific training and injury management programs to enhance the well-being of cricketers at all levels.